Evaluasi User Experience E-Learning Universitas Bhayangkara Jakarta Menggunakan Metode TUXEL: Technique for User eXperience Evaluation in E-Learning 2.0 - Alwan Fauzan; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The rapid development of Information and Communication Technology creates innovations in teaching and learning activities which are usually done face-to-face but can now be done anywhere without being bound by place and time using a Learning Management System by utilizing internet and computer technology. Based on a short user experience questionnaire to 159 users of E-Learning Universitas Bhayangkara Jakarta, it is known that the index score for the ease of learning and use factor is 72%; easy access 77%; interactive and non-boring visuals 68%; increase interest in learning 66%. TUXEL 2.0 is a method that is used specifically to evaluate the usability and user experience of an E-Learning using three questionnaires, namely problem reporting tables, general LMS evaluation, and user experience questionnaire for 12 respondents. From the results of the usability inspection stage, 33 problems were found from the four categories, namely Login, Assignments, General Interface, and Assessments. In the General LMS / Pedagogical Usability Inspection stage, 17 problems were found from the four categories, namely Learning Through LMS, LMS Flexibility, Help and Documentation, and LMS Learnability. At the UX Evaluation stage, the overall scale value tends to be positive. Based on the results of the hierarchical analysis of user needs, Ubhara Jaya's E-Learning is considered good enough to support learning activities, but is less reliable because it often experiences technical problems. Keywords: TUXEL 2.0, Learning Management System, Usability, User Experience